Estrategias de marketing para mejorar las ventas de la Empresa Mundo Libro en el distrito de Trujillo 2015. - Rujel Moreyra, Rayza Indira (2015)
This research was developed in order to determine the impact of marketing strategies to improve sales of the company World Book. For this report the descriptive research design was used, and the following methods: inductive; interview and survey: and finally the following research techniques were applied. Of which surveyed a sample of 62 clients and the respective interview the manager of the company World Book. From research primary information of customers who showed us their needs and provided its recommendations for the company to take into account when developing their marketing mix and can make a differentiation from its current competition was obtained, it will be reflected in a higher sales level. Once completed the process of research and analyzed the two variables, I conclude that a proper marketing strategy if it influences the improvement of the level of sales as long as the focus is directed to establish prices and offering attractive promotions for purchases made.